A Comparison of Bonding Parameter of Rare Earth Complexes in Different Amino-acids - Deepmala (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The absorption spectra of Neodymium and Erbium are recorded in visible region by taking Glycine and Arginine as primary ligand and Thiourea as a secondary ligand in the molar ratio1:2:1. In case of rare-earth complexes induced electric dipoles are responsible for the f-f transitions. Some transitions are arising due to electric as well as magnetic field. Energy levels corresponding to different peaks of Neodymium and Erbium can be expressed in terms of Slater Condon‟s and Lande‟s parameters. In Neodymium complexes ten peaks and in Erbium complexes eight peaks are observed in visible region. After complexation values of Slater Condon‟s and Lande‟s parameters decrease as there is expansion of central metal ion on complexation. By using Taylor‟s series expansion these parameters are calculated. Bonding parameter corresponding to these complexes also depends on Slater-Condon‟s and Lande‟s Parameters. In case of Neodymium: Glycine: thiourea bonding parameter is 0.1269707 but in Arginine it is 0.10997. In Arginine complex with Neodymium bonding parameter is less which indicates less involvement of 4f orbital. In Neodymium complexes bonding parameter is not real therefore all complexes of this rare-earth show ionic bonding. In case of Erbium: Glycine: thiourea bonding parameter is 0.6959 but in Arginine it is 0.712. In Arginine complex with Erbium bonding parameter is real for all complexes of this rare-earth and hence shows covalent bonding.